2016
DOI: 10.1371/journal.pone.0146601
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence Imaging of Superoxide Anion Detects Beta-Cell Function and Mass

Abstract: Superoxide anion is produced during normal cellular respiration and plays key roles in cellular physiology with its dysregulation being associated with a variety of diseases. Superoxide anion is a short-lived molecule and, therefore, its homeostatic regulation and role in biology and disease requires dynamic quantification with fine temporal resolution. Here we validated coelenterazine as a reporter of intracellular superoxide anion concentration and used it as a dynamic measure both in vitro and in vivo. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Therefore, most chemiluminescence studies are related to imaging ROS. Nonetheless, some chemiluminescence probes have an auto-oxidation feature, which is not reliant on ROS 16 , 17 . In this report, a chemiluminescence probe is designed, and we term it as ADLumin-1.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most chemiluminescence studies are related to imaging ROS. Nonetheless, some chemiluminescence probes have an auto-oxidation feature, which is not reliant on ROS 16 , 17 . In this report, a chemiluminescence probe is designed, and we term it as ADLumin-1.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that oxidative stress can affect testicular functions important for spermatogenesis (Zhang et al, 2013). ROS including superoxide anion are highly reactive intermediates best known for their ability to induce cellular damage (Bronsart et al, 2016). The quantification of superoxide anion production has been commonly used to assess adverse environmental conditions and pathogenesis of various chronic diseases including cancer and inflammation (Finkel and Holbrook, 2000;Waris and Ahsan, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that post-prandial hyperglycemia can occur in both healthy and insulin-resistant individuals. With this understanding, Bronsart et al [ 79 ] pioneered the detection of using a chemiluminescent probe to determine the effects of transient post-prandial hyperglycemia and evaluate whether the concentration of is physiologically involved. To do so, they measured the chemiluminescence from the interaction between in beta cells and coelenterazine (sensing enzyme) in mice with and without hyperglycemia.…”
Section: Superoxide Radical ( Detectionmentioning
confidence: 99%